The Online Brothel. Homosociality and Masculinities Among Men Who Pay for Sex in Argentina. - Morcillo, Santiago (2023)
For many heterosexual men, the sexual market, in addition to offering sex, has offered spaces for homosocial exchanges, and as such suspected of reproducing gender asymmetries. However, in the last decade these spaces have been transformed in their forms of visibility and accessibility. In this period online sites emerged and consolidated as places where men who pay for sex exchange experiences and socialize. Based on a virtual ethnography carried out in the two most important online forums in Argentina, this article analyzes forms of homosociality in these virtual spaces, and their links and tensions with different forms of masculinity. The analysis articulates the dynamics of homosocial sharing and its transformations in online forums, taking into account the role of the sexual market economy itself. The aim is to understand the links between these forms of homosociality, the reproduction (or not) of the patterns that sustain gender asymmetries and the specific characteristics of the interaction between men in the online world.